Preparation of porous carbides by reactive sintering - ZHANG Lei; PANG Xiao-lu; GAO Ke-wei (工程科学学报, 2015)
Three porous carbide ceramics (Cr3C2, TiC and WC) were successfully prepared through a reactive sintering process by reducing their oxides (Cr2O3, TiO2 and WO3) with methane. The surface and cross section morphologies of sintered products were examined by scanning electron microscopy, the microstruetures were characterized, and the reaction dynamics was studied by X-ray diffraction analysis. It is found that the preparation temperatures of porous TiC and WC ceramics should he 1200℃ and 1000℃, respectively, below which intermediates will be produced in the sintering process. The average sizes of both the ceramic struts and pores for porous Cr3C2 ceramics prepared by reactive sintering increase with an increase in sintering temperature.